(untitled) (Journal of Economic Research & Business Administration, 2018)
The article considers methodology of analysis of inventories, which will allow organizations to increase the efficiency of economic activities on the basis of revealing of intraindustrial reserves. To increase the efficiency use of production resources in the enterprise need to analyze the trends of these indicators, plan performance on their level, to calculate the influence of factors on their growth, count the indicators characterizing the work of the enterprise, the cost of commodity production, profit and profitability. Currently, much attention is paid to the analysis of inventories, as the information obtained as a result of this analysis is necessary to find ways to improve the efficiency of the enterprise. The information obtained during the analysis of material and production stocks allows to reveal in due time need for material and production stocks, and also to calculate efficiency of their use and many other indicators. Material and production stocks are a necessary element of functioning of any enterprise therefore results of economic activity of the organization depend on the correct accounting and the analysis of material and production stocks. The article discusses the importance of economic analysis, inventories in the enterprises. Studied various methods to analyze stocks, summarizes the steps of the analysis of inventories.